Bacterial Brain Abscess - Patel, Kevin (SAGE Publications, 2014)
Significant advances in the diagnosis and management of bacterial brain abscess over the past several decades have improved the expected outcome of a disease once regarded as invariably fatal. Despite this, intraparenchymal abscess continues to present a serious and potentially life-threatening condition. Brain abscess may result from traumatic brain injury, prior neurosurgical procedure, contiguous spread from a local source, or hematogenous spread of a systemic infection. In a significant proportion of cases, an etiology cannot be identified. Clinical presentation is highly variable and routine laboratory testing lacks sensitivity. As such, a high degree of clinical suspicion is necessary for prompt diagnosis and intervention. Computed tomography and magnetic resonance imaging offer a timely and sensitive method of assessing for abscess. Appearance of abscess on routine imaging lacks specificity and will not spare biopsy in cases where the clinical context does not unequivocally indicate infectious etiology. Current work with advanced imaging modalities may yield more accurate methods of differentiation of mass lesions in the brain. Management of abscess demands a multimodal approach. Surgical intervention and medical therapy are necessary in most cases. Prognosis of brain abscess has improved significantly in the recent decades although close follow-up is required, given the potential for long-term sequelae and a risk of recurrence.